BUKTI - BUKTI SUNGAI SEBAGAI JALUR TRANSPORTASI DAN ARAH ORIENTASI BANGUNAN (STUDI KASUS KAMPUNG MELAYU SEMARANG) - Fariz Addo Giovano; Agung Budi Sardjono (Prodi Arsitektur UNIVERSITAS KEBANGSAAN, 2024)
Abstract: Before the construction of the Daendels postal highway from Anyer to Panarukan in 1809-1819, spanning 10,000 km, rivers served as the primary mode of transportation. Urban centres in Java develop along the coastline and extend in linear patterns following the river. Similarly, Semarang is located in Central Java. The city has expanded in the coastal area, identified as Kampung Melayu in a 1695 map. This village serves as a port for sailors and new residents. The presence of harbours, markets, and mosques in villages signifies the nation's transition into the era of Islam's expansion. Following the completion of the Post highway and the ongoing sedimentation process, the river is no longer suitable for navigation. This study presents findings on using rivers for transportation and the proximity of various buildings to waterways. Field survey methods and historical archives indicate that the port, market, and mosque are situated along the river bank with direct access from the river. Keyword: river, sedimentation, postal highway.Abstrak: Sebelum dibangunnya jalan raya pos Daendels dari Anyer ke Panarukan pada tahun 1809-1819, sepanjang 10.000 km, sungai berfungsi sebagai moda transportasi utama. Pusat perkotaan di Jawa berkembang di sepanjang garis pantai dan terbentang dalam pola linier mengikuti aliran sungai. Begitu pula dengan Semarang yang terletak di Jawa Tengah. Kota ini berkembang di wilayah pesisir, sesuai dengan wilayah Kampung Melayu seperti yang digambarkan pada peta tahun 1695. Kampung ini berfungsi sebagai penghubung bagi para pelaut dan pemukim. Kehadiran kampung multi etnis dengan pelabuhan, pasar, dan masjid menandakan transisi bangsa dalam penyebaran Islam. Setelah selesainya Jalan Raya Pos dan proses sedimentasi yang sedang berlangsung, sungai tersebut tidak lagi layak untuk navigasi. Makalah ini menyajikan temuan mengenai pemanfaatan sungai untuk transportasi dan bukti keberadaan bangunan yang memiliki akses sungai pada masanya. Metode survei lapangan serta arsip sejarah menunjukkan bahwa foto kuno masjid dan beberapa bangunan di sekitarnya terletak di tepi sungai dengan akses dari sungai.Kata Kunci: sungai, sedimentasi, jalan raya pos.